1994
DOI: 10.1016/s0886-3350(13)80657-8
|View full text |Cite
|
Sign up to set email alerts
|

Clear lens extraction and intraocular lens implantation in a patient with bilateral anterior lenticonus secondary to Alport’s syndrome

Abstract: We describe bilateral phacoemulsification and implantation of foldable silicone intraocular lenses in a 25-year-old woman with Alport's syndrome and severe anterior lenticonus. Contrary to previous reports of lens capsule fragility in Alport's syndrome, this patient had relatively tough capsules, as do most patients her age. Apart from the tough capsules and positive pressure, which required the use of a viscoelastic to maintain the anterior chamber, the surgeries were unremarkable. The patient achieved excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Clear lens phacoemulsification has been shown to be an excellent surgical procedure for the treatment of anterior lenticonus in patients with Alport syndrome, allowing for rapid visual rehabilitation. 3,13 Kato et al 14 reported a case of anterior lenticonus that was treated with phacoemulsification and intraocular lens implantation. They advised caution while attempting intraocular lens implantation into the lens capsule of patients with Alport syndrome as the lens capsule may be …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear lens phacoemulsification has been shown to be an excellent surgical procedure for the treatment of anterior lenticonus in patients with Alport syndrome, allowing for rapid visual rehabilitation. 3,13 Kato et al 14 reported a case of anterior lenticonus that was treated with phacoemulsification and intraocular lens implantation. They advised caution while attempting intraocular lens implantation into the lens capsule of patients with Alport syndrome as the lens capsule may be …”
Section: Discussionmentioning
confidence: 99%
“…3 This protein is probably common to the basement membranes of the glomerulus, cochlea, retina, lens capsule and cornea. About 80% of those with Alport syndrome have the Xlinked form of the disease, which is caused by mutations in COL4A5, the gene encoding the α5 chain of type IV collagen.…”
Section: Introductionmentioning
confidence: 99%
“…7 As the major component of basement membranes in the human body, collagen type IV is composed of 6 genetically distinct chains; namely, alpha 1 to alpha 6. 2 These 6 chains are encoded by genes COL4A1 to COL4A6, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Occasional reports of traumatic and nontraumatic rupture of the anterior capsule have prompted some surgeons to treat anterior lenticonus more aggressively, with clear lens extraction. 7,8 However, we were reluctant to suggest clear lens extraction in the right eye of our patient because his corrected visual acuity was 20/25. After the right eye progressed quickly to lens rupture and total cataract, we were quicker to proceed with clear lens extraction in the left eye.…”
Section: Discussionmentioning
confidence: 87%